Notes on morphology and ecology of an elusive water flea Rhynchotalona latens (Sarmaja-Korjonen, Hakojärvi & Korhola, 2000) (Crustacea: Cladocera) - Sinev, Artem Y.; Dadykin, Ivan A. (Zootaxa, 2022)
Very rare North European water flea Rhynchotalona latens (Sarmaja-Korjonen, Hakojärvi & Korhola, 2000) (Crustacea: Cladocera), found mostly as remains during subfossil studies, was found in North Karelia, Russia. The species inhabits waterlogged Sphagnum mosses at lake margins, but is not present in littoral zones of the lakes. Morphology of thoracic limbs of R. latens was studied for the first time; SEM studies of the species were conducted for the first time. Our data suggests that R. latens is a specialized interstitial moss-dwelling species, only accidentally found in open water, which explains its rarity in samples taken by standard sampling methods. Presence of R. latens subfossil remains in sediments specifically indicate presence of Sphagnum at the lake coast, typical for acid oligotrophic or dystrophiс lakes.